Thiamine and Thiamine Pyrophosphate as Non-Competitive Inhibitors of Acetylcholinesterase—Experimental and Theoretical Investigations - Łukasz Szeleszczuk; Dariusz Maciej Pisklak; Błażej Grodner (Molecules, 2025)
Vitamin B1 (thiamine) plays an important role in human metabolism. It is essential for the proper growth and development of the body and has a positive effect on the functioning of the digestive, cardiovascular, and nervous systems. Additionally, it stimulates the brain and improves the psycho-emotional state. In vivo, vitamin B1 occurs in free form as thiamine or as its ester with phosphate residue(s), i.e., as mono-, di-, or triphosphate. It has been proven that supportive therapy with vitamin B1 can not only provide neuroprotection but also has a positive effect on advanced neurodegenerative diseases, such as Parkinson’s disease, Alzheimer’s disease, Wernicke–Korsakoff syndrome, or Huntington’s disease. This paper presents studies on the effect of free thiamine (T) and thiamine pyrophosphate (TPP) on the activity of acetylcholinesterase (AChE), which is an enzyme considered to play an important role in the therapies for neurodegenerative diseases, especially Alzheimer’s disease. The mechanisms of action of these compounds as potential inhibitors of AChE were evaluated using both experimental (enzymatic activity) as well as computational (molecular docking, molecular dynamics simulations, and MM-GBSA calculations) methods. The results of the current study indicate a non-competitive type of enzyme inhibition, in contrast to the previously published works suggesting a competitive one.